Presentación - Ballén Cifuentes, Oscar Alexander (Educación y Ciudad, 2021)
<iframe style="border: none; overflow: hidden;" src="https://www.facebook.com/plugins/video.php?height=314&href=https%3A%2F%2Fwww.facebook.com%2Fidep.bogota%2Fvideos%2F253004653457700%2F&show_text=false&width=560&t=0" width="560" height="314" frameborder="0" scrolling="no" allowfullscreen="true">